Maternal Vitamin D Status During Pregnancy and Bone Mass in Offspring at 20 Years of Age: A Prospective Cohort Study. (May 2014) - Zhu, Kun; Whitehouse, Andrew JO; Hart, Prue H; Kusel, Merci; Mountain, Jenny; Lye, Stephen; Pennell, Craig; Walsh, John P
ABSTRACT It is uncertain whether the vitamin D status of pregnant women influences bone mass of their children. Cohort studies have yielded conflicting results; none have examined offspring at skeletal maturity. This longitudinal, prospective study investigated the association between maternal vitamin D status and peak bone mass of offspring in 341 mother and offspring pairs in the Western Australian Pregnancy Cohort (Raine) Study. Maternal serum samples collected at 18 weeks gestation were assayed for 25‐hydroxyvitamin D (25OHD). Outcomes were total body bone mineral content (BMC) and bone mineral density (BMD) measured by dual‐energy X‐ray absorptiometry in offspring at 20 years of age. The mean (± SD) maternal serum 25OHD concentration was 57.2 ± 19.2 nmol/L; 132 women (38.7%) were vitamin D‐deficient (25OHD <50 nmol/L). After adjustment for season of sample collection, maternal factors, and offspring factors (sex, birth weight, and age, height, lean mass, and fat mass at 20 years), maternal 25OHD concentration was positively associated with total body BMC and BMD in offspring, with a mean difference of 19.2 (95% confidence interval [CI], 5.6–32.7) g for BMC and 4.6 (95% CI, 0.1–9.1) mg/cm2 for BMD per 10.0 nmol/L of maternal 25OHD. Maternal vitamin D deficiency was associated with 2.7% lower total body BMC (mean ± SE) (2846 ± 20 versus 2924 ± 16 g, p = 0.004) and 1.7% lower total body BMD (1053 ± 7 versus 1071 ± 5 mg/cm2, p = 0.043) in the offspring. We conclude that vitamin D deficiency in pregnant women is associated with lower peak bone mass in their children. This may increase fracture risk in the offspring in later life. © 2014 American Society for Bone and Mineral Research.